Comparison of the Sensitivity of 68Ga-DOTATATE PET/CT with Other Imaging Modalities in Detecting Head and Neck Paraganglioma: Experience from Western India - Dodamani, Manjunath Havalappa; Jaiswal, Sanjeet Kumar; Sarathi, Vijaya; Marfatia, Hetal; D'Cruz, Anil; Malhotra, Gaurav; Hira, Priya; Patil, Virendra A.; Lila, Anurag R.; Shah, Nalini S.; Bandgar, Tushar R. (World Journal of Nuclear Medicine, 2022)
Background This study aimed to compare the sensitivity of 68Ga-DOTATATE positron emission tomography/computed tomography (PET/CT) with other imaging modalities in the detection of head and neck paraganglioma (HNPGL).Methods The data of consecutive HNPGL patients (n = 34) who had undergone at least 68Ga-DOTATATE PET/CT and anatomical imaging (contrast-enhanced computed tomography/magnetic resonance imaging [CECT/MRI]) were retrospectively reviewed. The diagnosis of HNPGL (the primary tumor) was confirmed either by histopathology (n = 10) or was based on clinical follow-up and correlation of anatomical with functional imaging in whom histopathology was not available (n = 24). The sensitivities of 68Ga DOTATATE PET/CT, 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG-PET/CT), 131I-metaiodobenzylguanidine (131I-MIBG) scintigraphy, and CECT/MRI for primary HNPGL, associated primary pheochromocytoma + sympathetic paraganglioma (PCC + sPGL), and metastatic lesions were analyzed.Results Thirty-four patients (males: 15) [isolated HNPGL: 26, HNPGL + PCC: 04, HNPGL+ sPGL: 03, HNPGL + PCC + sPGL: 01] harboring 50 primary lesions were included. For total lesions, 68Ga-DOTATATE PET/CT (99.3%) had significantly higher lesion-wise sensitivity than 18F-FDG PET/CT (81.6%, p = 0.0164), 131I-MIBG (15.2%, p ≤0.0001), CECT (46.3%, p ≤ 0.0001) but similar sensitivity as MRI neck (97%, p = 0.79). On head-to-head comparison (21 primary HNPGL and 39 metastatic lesions), 68Ga DOTATATE PET/CT had significantly higher lesion-wise sensitivities for the detection of metastatic (100 vs. 71.9%, p = 0.04) and total lesions (100 vs. 77.2%, p ≤ 0.0001).Conclusion 68Ga-DOTATATE PET/CT was the most sensitive imaging modality for the detection of HNPGL and related lesions with significantly higher lesion-wise sensitivities than those of 18F-FDG PET/CT, 131I-MIBG, and CECT.
Keywords: head and neck paraganglioma; 68Ga-DOTATATE PET/CT; 18F-FDG-PET/CT